(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
In this study, the scope was to conduct an analysis of Doctoral dissertations produced in the Brazilian Graduate Programs in Education, in the Education Policy research lines, from 2013 to 2016, in order to verify the continuity or discontinuity of epistemological weaknesses in Doctoral dissertations. The research problem was: Are the theoretical-methodological weaknesses in Doctoral dissertations about Education Policy pointed out by the literature present from 2013 to 2016? It was concluded that there is a continuity regarding the difficulty of explaining the theoretical dimension of the research, a greater ease in the explanation of some elements of the methodological dimension and a tendency of permanence of weaknesses in the academic field of Education Policy. Keywords: Education Policy. Epistemological fragility. Theoretical dimension. Methodological dimension.